INTRODUCTION TO HTML5 Advanced APIs - Ruse, Kevin (Kevin Ruse and Associates Inc., 2016)
This book will quickly bring your HTML skills to the next level by introducing JavaScript implementation of the latest HTML Application Programming Interfaces. Upgrade your skills for both mobile and desktop Website and Web application development by learning how to access the user's full-screen, battery power and more. New and easy-to-use APIs even let your website or application respond to user voice commands. Other topics include: vibration, notifications, audio, video, accelerometer, web storage, drag and drop, AJAX level 2, web sockets, server-sent events, canvas, geolocation, web workers, device orientation, making website content editable, making entire web pages editable, voice recognition, voice synthesis and form validation. Each chapter includes demonstrations, hands-on exercises and code explanations. Students should be well versed in writing HTML and have some knowledge of JavaScript. Learn how to build better websites and web applications with Introduction to HTML5 Advanced APIs.